Co-based superelastic alloy material, plate material and wire material made of Co-based superelastic alloy material, manufacturing method of Co-based superelastic alloy material, stent, guide wire, and artificial hip joint

By optimizing the composition of Co-Cr-Al-Si alloy, the problem that existing biomaterials are difficult to achieve low Young's modulus and high wear resistance at the same time is solved, and the alloy is excellent superelastic properties and adaptability are achieved, which are suitable for a variety of biomaterial applications.

JP7669067B2Active Publication Date: 2025-04-28TOHOKU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023529556
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-06-23
Filing Date
2022-03-15
Publication Date
2025-04-28
Estimated Expiration
2042-03-15

AI Technical Summary

Technical Problem

Existing biomaterials have difficulty achieving low Young's modulus and high wear resistance, resulting in problems of stress shielding and bone atrophy in orthopedic implants.

Method used

By optimizing the composition of the Co-Cr-Al-Si alloy, controlling its composition within the range of points A to E in the Co-Cr-(Al,Si) pseudo-ternary phase diagram, it ensures that the alloy has a β-phase volume fraction of 50% or higher and excellent superelastic properties.

Benefits of technology

The Co-based superelastic alloy has excellent workingability, superelastic properties and wear resistance, and can adjust Young's modulus according to the crystal direction, making it suitable for a variety of biological materials applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669067000007
    Figure 0007669067000007
  • Figure 0007669067000008
    Figure 0007669067000008
  • Figure 0007669067000009
    Figure 0007669067000009
Patent Text Reader

Abstract

This Co-based superelastic alloy material comprises a Co-Cr-Al-Si-based alloy, wherein the composition (at%) is within the range of a pentagon formed by five points in a phase diagram of the Co-Cr-(Al,Si) pseudo-ternary phase system, said five points being point A: Co49.5Cr27.5(Al,Si)23, point B: Co57Cr27.5(Al,Si)15.5, point C: Co50Cr45(Al,Si)5, point D: Co45Cr45(Al, Si)10, and point E: Co45Cr32(Al,Si)23, Al is 2.5-10.0 at%, and Si is 2.5-13.0 at%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a Co-based superelastic alloy material, plate material and wire material made of a Co-based superelastic alloy material, a manufacturing method of a Co-based superelastic alloy material, a stent, a guidewire and an artificial hip joint, and in particular to a Co-based superelastic alloy material, plate material and wire material made of a Co-based superelastic alloy material, and a manufacturing method of a Co-based superelastic alloy material that are suitable as a biomaterial. This application claims priority based on Japanese Patent Application No. 2021-104095, filed on June 23, 2021, the contents of which are incorporated herein by reference. [Background technology]

[0002] Stainless steel, Co-Cr alloys, and Ti alloys are widely used as biomaterials. For example, bone substitute implant materials are desired to have a low Young's modulus similar to that of bone to prevent stress shielding. Here, stress shielding refers to the phenomenon in which, when an implant material with a higher Young's modulus than living bone is used, stress is preferentially applied to the implant material, shielding the stress applied to the surrounding bone. When stress shielding occurs, bone atrophy occurs, leading to problems such as a decrease in bone mass.

[0003] In recent years, β-Ti alloys have been attracting attention as a material capable of achieving a low Young's modulus of approximately 50 GPa. However, although β-Ti alloys have a low Young's modulus, they have poor wear resistance, and there are concerns that they may be damaged by wear when used as biomaterials.

[0004] On the other hand, Co-Cr alloys are known to have excellent wear resistance, but because the Young's modulus of Co-Cr alloys is extremely high, about 10 times that of living bone, there is a problem of stress shielding when using Co-Cr alloys as biomaterials.

[0005] Thus, low Young's modulus and wear resistance are mutually exclusive properties, and it has been extremely difficult to develop a biomaterial that can achieve both of these properties.

[0006] Meanwhile, shape memory alloys are being put to practical use in various industrial and medical fields to utilize their unique functions. Among them, Ti-Ni alloys, Ni-Al alloys, Cu-Zn-Al alloys, Cu-Al-Ni alloys, etc. are known as shape memory alloys with excellent superelastic properties, and Ti-Ni alloys are particularly useful as biomaterials.

[0007] Furthermore, Patent Document 1 discloses a Cu-Al-Mn alloy having a recrystallized structure consisting of a single β phase as an alloy having excellent superelastic properties. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent No. 6490608 [Non-patent literature]

[0009] [Non-Patent Document 1] K. Hirata, X. Xu, T. Omori, M. Nagasako, and R. Kainuma, Journal of Alloys and Compounds 642(2015) 200-203. [Non-Patent Document 2] T. Odaira, X. Xu, A. Miyake, T. Omori, M. Tokunaga, and R. Kainuma, Scripta Materialia 153(2018) 35-39. [Non-Patent Document 3] T. Odaira, X. Xu, T. Omori, and R. Kainuma. The 6th International Conference on Ferromagnetic Shape Memory Alloys, 2019, 164, ISBN 978-80-905962-9-0. [Non-Patent Document 4] K. Hirata, X. Xu, T. Omori, and R. Kainuma, Journal of Magnetism and Magnetic Materials 500(2020)166311. [Non-Patent Document 5] T. Odaira, X. Sheng, X. Xu, T. Omori, and R. Kainuma, Applied Physics Reviews 7 (2020) 031406. Summary of the Invention [Problem to be solved by the invention]

[0010] As described above, low Young's modulus and wear resistance are mutually exclusive properties, and thus there has been no biomaterial that combines these properties.

[0011] In addition, Ti-Ni alloys have been put to practical use as biomaterials with excellent superelastic properties, but their applications are limited due to their poor processability. In addition, Ni allergies are a concern, so the development of Ni-free superelastic materials is desired. In this regard, β-Ti alloys, which have a low Young's modulus, are Ni-free, but their superelastic strain is very small at around 3%.

[0012] In addition, the Cu-Al-Mn alloy described in Patent Document 1 has excellent superelastic properties, but is not suitable as a biomaterial. Therefore, there is a strong demand for the development of a biomaterial having excellent superelastic properties.

[0013] In addition, it is difficult to coarsen the crystal grains of the Co-Cr-Al-Si alloys described in Non-Patent Documents 1 to 5, and it has not been possible to produce large single crystals, for example, exceeding 1 cm. Furthermore, the Co-Cr-Al-Si alloy described in Non-Patent Document 5 is brittle and has poor workability, with a rolling reduction rate of only 20%.

[0014] In view of the above, the present invention aims to provide a Co-based superelastic alloy material that is excellent in processability, superelasticity, and wear resistance, and is capable of exhibiting different Young's moduli depending on the crystal orientation. Further, the present invention aims to provide a plate material and wire material made of such a Co-based superelastic alloy material, a manufacturing method for the Co-based superelastic alloy material, a stent, a guidewire, and an artificial hip joint. [Means for solving the problem]

[0015] The present inventors first focused on the composition of Co-based alloys and investigated composition design from the viewpoints of superelasticity, wear resistance, and Young's modulus. As a result, they discovered that, by controlling the content of each component in an alloy containing Co, Cr, Al, and Si (hereinafter also referred to as a Co-Cr-Al-Si alloy) within an appropriate range, it is possible to realize a Co-based superelastic alloy material that is excellent in workability, superelasticity, and wear resistance, and can exhibit different Young's moduli depending on the crystal orientation, and thus completed the present invention.

[0016] The present invention has been made based on the above findings, and the gist of the present invention is as follows. [1] The Co-based superelastic alloy material according to one embodiment of the present invention is a Co-based superelastic alloy material made of a Co-Cr-Al-Si alloy, and the composition (atomic %) is as follows: Point A: Co on a Co-Cr-(Al,Si) pseudo ternary phase diagram. 49.5 Cr 27.5 (Al,Si) 23 , Point B: Co 57 Cr 27.5 (Al,Si) 15.5 , C point: Co 50 Cr 45 (Al,Si)5, D point:Co 45 Cr 45 (Al,Si) 10 , and point E: Co 45 Cr 32 (Al,Si) 23 The content of Al is 2.5 to 10.0 atomic % and the content of Si is 2.5 to 13.0 atomic %. [2] In the Co-based superelastic alloy material described in [1] above, the main phase of the metal structure may be a β phase with a BCC structure. [3] In the Co-based superelastic alloy material according to the above [1] or [2], the volume fraction of the β phase of the BCC structure may be 50% or more. [4] The Co-based superelastic alloy material described in [2] or [3] above may contain, in addition to the main phase, one or more phases selected from the group consisting of a γ phase with an FCC structure, an ε phase with an HCP structure, and a σ phase, in a total amount of 50 volume % or less. [5] In the Co-based superelastic alloy material described in [2] to [4] above, the crystal structure of the β phase may be composed of one or more phases selected from the group consisting of an A2 phase, a B2 phase, and an L21 phase. [6]Top Note [ In the Co-based superelastic alloy material described in [5], the B2 phase may account for 20 volume % or more of the β phase.

[0017] [7] One embodiment of the present invention provides a plate material made of the Co-based superelastic alloy material described in any one of [1] to [6] above, wherein the average crystal grain size of the Co-based superelastic alloy material is equal to or greater than the thickness of the plate material. [8] One embodiment of the present invention provides a wire made of the Co-based superelastic alloy material described in any one of [1] to [6] above, wherein the average crystal grain size of the Co-based superelastic alloy material is equal to or greater than the radius of the wire.

[0018] [9] A method for producing a Co-based superelastic alloy material according to one embodiment of the present invention is a method for producing a Co-based superelastic alloy material as described in any one of the above [1] to [6], and includes a solution heat treatment step of performing heat treatment at 1100°C to 1400°C.

[10] The method for producing a Co-based superelastic alloy material described in [9] above may include a cooling step of cooling to room temperature at an average cooling rate of 5° C. / sec or more after the solution heat treatment step.

[11] Top Note [ In the method for producing a Co-based superelastic alloy material according to the above-mentioned method, and during the cooling step.The method may further include a grain coarsening process in which heat treatment is repeatedly performed in a temperature range where a single β phase is formed and a temperature range where a two-phase mixture of β phase + γ phase or β phase + σ phase is formed, or a three-phase mixture of β phase + γ phase + σ phase is formed.

[12] In the method for producing a Co-based superelastic alloy material described in

[11] above, the temperature range in which the β single phase occurs may be a temperature range of 1100 to 1400°C, and the temperature range in which the two phases occur or the temperature range in which the three phases occur may be a temperature range of 700 to 1100°C.

[13] A guidewire according to one embodiment of the present invention is made of a material containing the Co-based superelastic alloy material according to any one of the above [1] to [6].

[14] A stent according to one embodiment of the present invention is made of a material containing the Co-based superelastic alloy material according to any one of the above [1] to [6].

[15] An artificial hip joint according to one embodiment of the present invention is made of a material containing the Co-based superelastic alloy material described in any one of the above [1] to [6]. Effect of the Invention

[0019] According to the present invention, it is possible to provide a Co-based superelastic alloy material that is excellent in processability, superelasticity, and wear resistance, and is capable of exhibiting different Young's moduli depending on the crystal orientation, a plate material and a wire material made of the Co-based superelastic alloy material, and a method for producing the Co-based superelastic alloy material. Furthermore, the Co-based superelastic alloy material of the present invention can exhibit superelasticity properties superior to conventional materials, has excellent wear resistance, and can exhibit different Young's moduli by controlling the crystal orientation, so that it can be suitably used in a wide range of fields as a variety of biomaterials. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a phase diagram of the Co-Cr-(Al,Si) pseudo-ternary system. [Diagram 2] FIG. 2 shows a diffraction pattern (selected area diffraction pattern) of alloy No. 120 when an electron beam was incident in the [01-1] direction of the main phase (β phase). [Diagram 3] 3(a) to (d) are electron microscope images of Alloy No. 120. [Figure 4A] FIG. 4A is a diagram showing a temperature profile of the grain coarsening step (cyclic heat treatment) using Alloy No. 120. [Figure 4B] FIG. 4B shows the analysis results by EBSD for Sample 1 and Sample 2 shown in FIG. 4A. [Figure 5A] FIG. 5A is a diagram showing the temperature profile of the grain coarsening step (cyclic heat treatment) and the subsequent solution heat treatment step using Alloy No. 120. [Figure 5B] FIG. 5B shows the results of EBSD observation of a cross section parallel to the plate surface of a plate made of Alloy No. 120. [Figure 6] FIG. 6 shows the stress-strain curve of the single crystal specimen obtained from alloy No. 118. [Figure 7A] FIG. 7A is a stress-strain curve of a single crystal sample obtained from Alloy No. 120. [Figure 7B] FIG. 7B is a schematic diagram showing a tensile test piece used for measuring the stress-strain curve (SS curve) in this example. [Figure 8A] FIG. 8A shows the stress-strain curves of the single crystal samples obtained from alloys No. 118 and No. 120. [Figure 8B] FIG. 8B is a graph showing the relationship between Young's modulus and strain obtained from the stress-strain curve of FIG. 8A. [Figure 9] FIG. 9 shows the stress-strain curve of the single crystal specimen obtained from Alloy No. 120, and a graph showing the relationship between Young's modulus and strain obtained from the stress-strain curve. [Figure 10] FIG. 10 shows a photograph of the wear mark after the wear test and a photograph of its cross section. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The following describes the Co-based superelastic alloy material, the plate material and wire material made of the Co-based superelastic alloy material, and the manufacturing method of the Co-based superelastic alloy material according to this embodiment. However, the present invention is not limited to the configuration disclosed in this embodiment, and various modifications are possible without departing from the spirit of the present invention.

[0022] [Co-based superelastic alloy material] First, the Co-based superelastic alloy material of this embodiment will be described in detail below. In this specification, unless otherwise specified, the content of each element is based on the entire alloy material (100 atomic %).

[0023] <Composition> The Co-based superelastic alloy material of this embodiment is made of Co, Cr, Al, Si, and unavoidable impurities, that is, the Co-based superelastic alloy material of this embodiment is made of a Co-Cr-Al-Si alloy.

[0024] The composition (atomic %) of the Co-based superelastic alloy material of this embodiment is shown in FIG. 1. On the Co-Cr-(Al,Si) pseudo-ternary phase diagram (where "(Al,Si)" is the sum of the compositions of Al and Si), point A is Co. 49.5 Cr 27.5 (Al,Si) 23 , Point B: Co 57 Cr 27.5 (Al,Si) 15.5 , C point: Co 50 Cr 45 (Al,Si)5, D point:Co 45 Cr 45 (Al,Si) 10 , and point E: Co 45 Cr 32 (Al,Si) 23 The composition is surrounded by a pentagon consisting of the five points, and the Al content is within the range of 2.5 to 10.0 atomic % and the Si content is within the range of 2.5 to 13.0 atomic %. Note that "the composition surrounded by a pentagon" refers to the composition on each side and inside the pentagon.

[0025] Here, in the case of a general ternary phase diagram, if it is assumed to be an "AB-C ternary system", each vertex of the triangle corresponds to 100% A, 100% B, and 100% C, respectively. However, in this embodiment, in order to specify the composition of the Co-Cr-Al-Si alloy, a pseudo-ternary phase diagram is used in which each of the three sides is defined to correspond to Co, Cr, and the sum of Al and Si. Also, each vertex of the pseudo-ternary phase diagram shown in FIG. 1 means, in atomic %, "40%Co-0%Cr-60%(Al,Si)", "100%Co-0%Cr-0%(Al,Si)", and "40%Co-60%Cr-0%(Al,Si)". Note that each vertex is "Co 40 (Al,Si) 60 " "Co 100 " and "Co 40 Cr 60 "It can also be written as ".

[0026] The Co-based superelastic alloy material of this embodiment is substantially free of components other than Cr, Al, Si, and Co. Here, "substantially free" means including the presence of unavoidable impurities to a degree that does not impair the effects and characteristics of the present invention. Inevitable impurities are components that are mixed in due to various factors in the manufacturing process, including raw materials, when the alloy material is industrially manufactured, and also include components that are inevitably mixed in. The content of unavoidable impurities is preferably as low as possible, but is preferably less than 1.0 mass% with respect to the total mass of the alloy material.

[0027] By adjusting the composition within the pentagon of points A to E, it is possible to provide a Co-based superelastic alloy material that is excellent in workability, superelastic properties, and wear resistance, and that can exhibit different Young's moduli depending on the crystal orientation. If the composition is outside sides EA and AB, the workability decreases, and it becomes difficult to form coarse grains or single crystals. If the composition is outside side BC, the superelastic properties and Young's modulus properties decrease. If the composition is outside sides CD and DE, all of the superelastic properties, Young's modulus, and workability decrease.

[0028] Al is an element that has an effect of affecting the phase stability of the β phase and workability. In particular, in order to improve hot workability, it is necessary to control the Al content. In other words, the hot workability can be improved by adjusting the Al content. If the Al content is less than 2.5 atomic %, there is a risk that sufficient β phase cannot be obtained. Therefore, the Al content is set to 2.5 atomic % or more, preferably 4.5 atomic % or more, and more preferably 5.0 atomic % or more. On the other hand, if the Al content exceeds 10.0 atomic %, there is a risk that hot workability is deteriorated. Therefore, the Al content is set to 10.0 atomic % or less, preferably 9.0 atomic % or less, and more preferably 8.0 atomic % or less.

[0029] Like Al, Si is an element that has an effect of affecting the phase stability and workability of the β phase. In particular, in order to improve hot workability, it is necessary to control the Si content. That is, by adjusting the Si content, hot workability can be improved. If the Si content is less than 2.5 atomic %, there is a risk that sufficient β phase cannot be obtained. Therefore, the Si content is set to 2.5 atomic % or more, preferably 6.5 atomic % or more, and more preferably 7.0 atomic % or more. On the other hand, if the Si content exceeds 13.0 atomic %, there is a risk that hot workability is degraded. Therefore, the Si content is set to 13.0 atomic % or less, preferably 12.0 atomic % or less, and more preferably 11.0 atomic % or less.

[0030] The elements described above are the basic components contained in the Co-based superelastic alloy material according to this embodiment. That is, the Co-based superelastic alloy material according to this embodiment does not substantially contain any components other than Cr, Al, Si, and Co. Incidentally, inevitable impurities may be mixed in due to various factors in the manufacturing process, such as components derived from raw materials. As described above, the content of such inevitable impurities is preferably as small as possible, and is preferably, for example, less than 1.0 mass% with respect to the total mass of the alloy material.

[0031] <Metal structure> The metal structure of the Co-based superelastic alloy material of this embodiment is preferably a structure in which the β phase, which is a BCC structure, is the main phase. The "main phase" here means 50% by volume or more of the total metal structure of the Co-based superelastic alloy material. If the volume fraction of the β phase is less than 50%, sufficient superelastic properties may not be obtained. Furthermore, precise control of the Young's modulus for each crystal orientation may be difficult. Therefore, it is more preferable that the volume fraction of the β phase is 50% or more. In addition, in the Co-based superelastic alloy material of this embodiment, the degree of ordering of the β phase, which is the main phase, is reduced, and therefore it is considered that the hot workability described later is improved. Furthermore, the Co-based superelastic alloy material may be a single crystal having no grain boundaries between β phases.

[0032] From the viewpoint of fully exerting the superelastic properties and processability, the crystal structure of the β phase, which is the main phase, is preferably a crystal structure of one or more types selected from the group consisting of A2 type (A2 phase), B2 type (B2 phase) and L21 type (L21 phase). In order to further exert the effect, it is more preferable that the crystal structure of the main phase contains a large amount of B2 type. In order to fully ensure the superelastic properties, it is preferable that the crystal structure of the β phase is basically composed of a fine phase consisting of one or both of B2 type and L21 type. In this case, the fine phase is, for example, less than 10 nm. Note that the crystal structure of the β phase may contain A2 type, but if the volume fraction of A2 type increases, the superelastic properties will decrease. On the other hand, in order to fully ensure the processability, it is preferable that the crystal structure of the β phase is basically composed of a fine phase consisting of one or both of A2 type and B2 type. In this case, the fine phase is, for example, less than 10 nm. The β-phase crystal structure may contain L21 type, but if the volume fraction is high, the workability decreases. Therefore, the β-phase crystal structure may contain small amounts of A2 type and L21 type, but it is more preferable that it contains a large amount of B2 type. As described above, in order to sufficiently obtain both good superelasticity and processability, the proportion of B2 type in the β phase is preferably 20 volume % or more, more preferably 30 volume % or more, and even more preferably 40 volume % or more.

[0033] In addition to the main phase, a small amount of one or more of the γ phase of the FCC structure, the ε phase of the HCP structure, and the σ phase may be precipitated. The γ phase contributes to improving hot workability and making it easier to obtain coarse grains, but if it appears in large quantities, it may impair the superelastic properties. The ε phase contributes to improving the wear resistance and making it easier to obtain coarse grains, but if it appears in large quantities, it may impair the superelastic properties. The σ phase contributes to improving the wear resistance and making it easier to obtain coarse grains, but if it appears in large quantities, it may impair both the superelastic properties and the hot workability. For these reasons, when one or more of the γ phase, ε phase, and σ phase are precipitated in addition to the main phase described above in the metal structure of the Co-based superelastic alloy material, it is preferable that the total amount of these phases is 50 volume % or less.

[0034] [Method of manufacturing Co-based superelastic alloy material] The Co-based superelastic alloy material can be produced by ordinary methods, such as melting and casting, hot working (hot forging, hot rolling, etc.), and then performing a solution treatment in a specific temperature range described below. The production conditions for each step are not particularly limited, but for example, the temperature in the hot working can be 1100 to 1400°C, and the hot working rate can be 10% or more.

[0035] In the manufacturing method of the Co-based superelastic alloy material of this embodiment, after hot working, a solution treatment is performed. The solution treatment is performed by heating the Co-based superelastic alloy material that has been melted and cast, and then formed by hot working or the like to a solution temperature, converting the structure to a single phase β phase with a BCC structure, and then quenching. The solution treatment is performed at a solution temperature in the range of 1100 to 1400°C. Since the higher the solution treatment temperature, the easier it is to obtain a single phase β phase, the solution treatment is preferably performed at 1100 to 1400°C, which is close to the melting point.

[0036] The holding time at the solution temperature is not particularly limited, but is preferably 60 minutes or more from the viewpoint of sufficient temperature rise. However, if the holding time exceeds 24 hours, there is a risk of oxidation, so it is preferably 24 hours or less.

[0037] Here, when the crystal grains of the Co-based superelastic alloy material are coarsened to form coarse grains or single crystals, it is preferable to carry out a crystal grain coarsening step (cycle heat treatment) described below after the above-mentioned solution heat treatment step. That is, after the solution heat treatment step, the Co-based superelastic alloy material can be made coarse grains or single crystals by repeatedly performing heat treatment in a temperature range where the β phase becomes a single phase and a temperature range where the β phase + γ phase or the β phase + σ phase becomes two phases, or a temperature range where the β phase + γ phase + σ phase becomes three phases. The number of times of the crystal grain coarsening step is not limited to a plurality of times, and for example, the effect can be obtained even if it is performed only once. That is, after the above-mentioned solution heat treatment, the temperature may be cooled at an average cooling rate of a level described later to a temperature range where the β phase + γ phase or the β phase + σ phase becomes two phases, or a temperature range where the β phase + γ phase + σ phase becomes three phases, and then the temperature may be raised to a temperature range where the β phase becomes a single phase, and further maintained. This allows the Co-based superelastic alloy material to be made coarse grains or single crystals. However, in order to further coarsen the crystal grains or to produce larger single crystals, it is preferable to carry out the crystal grain coarsening step multiple times after the solution heat treatment step. Hereinafter, the case where the crystal grain coarsening step is carried out multiple times will be described in detail.

[0038] In the grain coarsening process (cycle heat treatment), first, the material is cooled from the above-mentioned solution temperature to a temperature range where the two phases are formed or the three phases are formed. Specifically, the material is cooled to a temperature range of 700 to 1100°C, which is the temperature range where the two phases are formed or the three phases are formed. From the viewpoint of efficiency, the average cooling rate at this time is preferably 0.1°C / min or more, more preferably 1°C / min or more. There is no particular upper limit to the average cooling rate, but it may be 20°C / min or less. Cooling is performed by placing the material in a coolant such as water, or by forced air cooling.

[0039] The material is then held in the temperature range where the two phases form or the three phases form, preferably for 1 minute to 24 hours. If the holding time is too long, oxidation may occur, so 24 hours or less is preferable. On the other hand, if the holding time is too short, precipitates of the γ phase, σ phase, or γ phase and σ phase cannot be sufficiently generated, so the holding time in the temperature range where the two phases form or the three phases form is preferably 1 minute or more.

[0040] After being held in the temperature range where the two phases are formed or the temperature range where the three phases are formed, the temperature is raised to the temperature range where the β phase is single phase and is further held. Specifically, the temperature is raised to the temperature range of 1100 to 1400°C, which is the temperature range where the β phase is single phase. The average heating rate at this time is not particularly limited, but from the viewpoint of easily obtaining coarse grains or single crystals, it is preferably 20°C / min or less, and more preferably 10°C / min or less. If the average heating rate is too low, there is a risk of efficiency decreasing, so it is preferably 0.1°C / min or more.

[0041] In this embodiment, the "average cooling rate" refers to the temperature drop of the alloy material from the start of cooling to the end of cooling divided by the time required from the start of cooling to the end of cooling, and the "average heating rate" refers to the temperature rise of the alloy material from the start of heating to the end of heating divided by the time required from the start of heating to the end of heating.

[0042] In order to make the Co-based superelastic alloy material coarse grained or single crystal, it is preferable to repeatedly heat treat the material in a temperature range where the material is a single β phase and a temperature range where the material is a two-phase range (β phase + γ phase or β phase + σ phase) or a three-phase range (β phase + γ phase + σ phase), as described above, with the number of repetitions being about 1 to 20. In other words, if one cycle of heat treatment is "cooling from the temperature range where the material is a single β phase to the temperature range where the material is a two-phase range or the temperature range where the material is a three-phase range and holding the temperature there, and then heating up to the temperature range where the material is a single β phase and holding the temperature there again", by repeating this cycle 1 to 20 times, the Co-based superelastic alloy material can be easily made coarse grained or single crystallized, and as a result, the effect of being able to produce coarse grained or single crystal can be enjoyed.

[0043] After the solution heat treatment process or the grain coarsening process (cycle heat treatment) after the solution heat treatment process, the temperature is kept in a range where the β phase becomes a single phase, and then cooled to room temperature (about 25°C) (cooling process). The cooling is performed by rapid cooling (for example, water cooling), so that the Co-based superelastic alloy material of this embodiment can be manufactured. Specifically, the average cooling rate during rapid cooling is preferably 5°C / sec or more. This makes it possible to reduce the amount of precipitates composed of one or more of the γ phase, ε phase, and σ phase, and further makes it possible to make the crystal structure of the β phase a crystal structure of one or more of the A2 type, B2 type, and L21 type. Specifically, by making the average cooling rate 5°C / sec or more, the proportion of the B2 phase in the β phase can be 20 volume % or more. Furthermore, in order to obtain a single β phase structure and to increase the proportion of B2 type in the crystal structure of the β phase, it is more preferable to set the average cooling rate during quenching to 100°C / s or more. By setting the average cooling rate during quenching to 100°C / s or more, a fine phase of less than 10 nm, which is B2 type, can be obtained. As a result, superelastic properties, low Young's modulus properties, and processability can be sufficiently ensured. Thus, when the average cooling rate during quenching is 100°C / s or more, A2 type and L21 type do not exist or their volume fractions are extremely small, which is preferable. On the other hand, when the average cooling rate during quenching is less than 100°C / s, a coarse phase of 10 nm or more consisting of one or both of A2 type and L21 type and having a volume fraction of less than 80% appears, and further, less than 50 volume% precipitates consisting of one or more of γ phase, ε phase, and σ phase appear from the grain boundary of the β phase. Even in such a case, relatively good superelastic properties, low Young's modulus properties, and processability can be obtained, but these properties are better in the case of a fine phase consisting of B2 type. Therefore, it is more preferable to set the average cooling rate during quenching to 100°C / sec or more. On the other hand, when the average cooling rate during quenching is less than 5°C / sec, coarse phases of 10 nm or more with a volume fraction of 80% or more consisting of either or both of the A2 and L21 types appear. Furthermore, precipitates of 50% or more by volume consisting of one or more of the γ, ε, and σ phases appear both at the grain boundaries and within the β phase. As a result, there is a risk of a significant decrease in superelastic properties, low Young's modulus properties, and workability.

[0044] [Characteristics] The Co-based superelastic alloy material according to this embodiment exhibits the following characteristics.

[0045] <Young's modulus> The Co-based superelastic alloy material of this embodiment has strong elastic anisotropy. That is, the Young's modulus of the Co-based superelastic alloy material of this embodiment is highly dependent on the crystal orientation. Therefore, the Co-based superelastic alloy material of this embodiment has a Young's modulus that differs depending on the crystal orientation. Specifically, <100> In the direction of the axial direction, the Young's modulus is 10 to 30 GPa, which is close to that of living bone. <110> Direction and <111> In the direction of the axial direction, the Young's modulus is relatively high, at 80 to 150 GPa, which is very stiff. <100> In the direction, etc., it exhibits a relatively low Young's modulus, while in the direction <110> Direction and <111> In the direction, etc., a relatively high Young's modulus is exhibited. Thus, the Young's modulus of the Co-based superelastic alloy material of this embodiment differs depending on the crystal orientation.

[0046] The Young's modulus of biological bone is about 10 to 30 GPa. In other words, if the Young's modulus of the Co-based superelastic alloy material can be reduced to the same level as that of biological bone, the Young's modulus will be close to that of biological bone, and stress shielding can be prevented when the Co-based superelastic alloy material is used as a biological material such as a bone substitute implant material. In other words, when the Co-based superelastic alloy material of this embodiment is applied to a biological material such as a bone substitute implant material, among the crystal orientations, <100> The Young's modulus can be reduced by using a Co-based superelastic alloy in which the direction is dominant.

[0047] On the other hand, for members such as stents and guidewires, a high Young's modulus of about 80 to 150 GPa is required. Therefore, when the Co-based superelastic alloy material of this embodiment is applied to members such as stents and guidewires, among the crystal orientations, <110> Direction and <111> The Young's modulus can be increased by using a Co-based superelastic alloy in which the direction is dominant.

[0048] As described above, in the Co-based superelastic alloy material according to this embodiment, there is a correlation between the crystal orientation and the resulting Young's modulus, so that even with the same material, different Young's moduli can be expressed simply by controlling the crystal orientation. In other words, by using the Co-based superelastic alloy material according to this embodiment, it is possible to produce a material with the desired crystal orientation and thereby express a Young's modulus according to the application. For example, <100> By making it a single crystal of the same orientation, the Young's modulus can be reduced, <111> The Young's modulus can be increased by making it into a single crystal of the same orientation.

[0049] In this embodiment, the Young's modulus of each crystal orientation can be calculated from the gradient of the stress-strain curve using a strain gauge. Specifically, a single crystal specimen with a specific crystal orientation is prepared, a strain gauge is attached to the specimen, and a stress-strain curve is experimentally determined by a tensile or compression test.The Young's modulus at any given strain is then calculated from the gradient of the stress-strain curve.

[0050] <Superelastic properties> The Co-based superelastic alloy material of this embodiment exhibits stable and excellent superelasticity, specifically, it can exhibit extremely large superelasticity with a superelastic strain of 3% or more. In this embodiment, the "superelastic strain" is defined as the strain amount in the plateau region in a stress-strain diagram as shown in Fig. 6. Here, the "plateau region" is a region following the elastic deformation region, and is a region of constant stress after yielding.

[0051] <Wear resistance> The Co-based superelastic alloy material of this embodiment has excellent wear resistance due to the optimization of the composition. Therefore, it can be suitably used as a biomaterial. The improvement of wear resistance can be achieved by optimizing the composition.

[0052] <Hot workability> In addition to the above-mentioned characteristics, the Co-based superelastic alloy material of this embodiment also has excellent hot workability, which is believed to be due to a decrease in the degree of order in the BCC structure. Conventional Co-Cr-Al-Si alloys have good superelastic properties, but are very brittle and difficult to process, leaving room for problems in terms of practical use. However, the Co-based superelastic alloy material of this embodiment has improved hot workability by reducing the Al and Si contents and lowering the degree of order in the ordered alloy.

[0053] [Materials (plates and wires)] The superelastic properties of Co-based superelastic alloys can depend not only on the crystal structure but also on the size of the crystal grains. For example, in the case of sheet or wire material, when the average crystal grain size of the crystal grains is equal to or greater than the thickness T of the sheet material or the radius R of the wire material, the superelasticity is greatly improved. This is thought to be because the binding force between the crystal grains is reduced when the average crystal grain size of the crystal grains is equal to or greater than the thickness T of the sheet material or the radius R of the wire material.

[0054] <Plate material> In a plate material made of a Co-based superelastic alloy, the average crystal grain size is preferably equal to or greater than the thickness T of the plate material. In a plate material having such crystal grains, each crystal grain is free from the grain boundary at the surface of the plate material. In addition, in a plate material having an average crystal grain size equal to or greater than the thickness T, the binding force between the crystal grains is reduced, as in the case of the wire material described above, and the plate material exhibits excellent superelasticity. In order to further reduce the binding force between the crystal grains and exhibit excellent superelasticity, it is more preferable that the average crystal grain size of the crystal grains of the plate material is equal to or greater than 2T. It is more preferable that the average crystal grain size of the crystal grains is equal to or greater than the width W of the plate material.

[0055] Plate materials made of Co-based superelastic alloys can be used for various spring materials, contact members, clips, etc., taking advantage of their superelasticity.

[0056] <Wire rod> In a wire made of a Co-based superelastic alloy, the average crystal grain size is preferably equal to or greater than the radius R of the wire. In order to further reduce the binding force between the crystal grains and approach single crystal behavior, it is more preferable that the average crystal grain size is equal to or greater than the diameter 2R.

[0057] Wires made of Co-based superelastic alloys can be used for stents and guide wires, for example. When the wires made of Co-based superelastic alloys are thin wires with a diameter of 1 mm or less, multiple thin wires may be twisted together to form a twisted wire. Furthermore, the wires can also be used as spring materials.

[0058] <Method of manufacturing plate and wire materials> The plate material made of the Co-based superelastic alloy material of this embodiment is produced by hot rolling, punching and / or pressing into a desired shape, and then performing at least one of the above-mentioned solution treatments, and optionally performing quenching and aging treatments.

[0059] The wire made of the Co-based superelastic alloy material of this embodiment is made into a wire by hot forging and drawing. After that, the wire is subjected to at least one solution heat treatment as described above, and then quenching and aging treatment are performed as necessary. By producing the wire by performing the same treatment as the plate material, it is possible to produce a wire with coarsened crystal grains whose average crystal grain size is equal to or larger than the radius.

[0060] [Application] The Co-based superelastic alloy material of this embodiment is suitable as a biomaterial for artificial hip joints, etc., because it can maintain a Young's modulus close to that of living bone. In addition, the Co-based superelastic alloy material of this embodiment has a Young's modulus that varies depending on the crystal orientation, and therefore exhibits a relatively high Young's modulus. <110> Direction and <111> By giving priority to the direction, etc., the material can be suitably used for stents, guide wires, etc. EXAMPLES

[0061] The present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention.

[0062] The alloy material having the composition shown in Table 1 was melted in an Ar atmosphere by high-frequency induction melting, and the melted material was cast into a metal mold to produce a round bar specimen (φ10 mm). The obtained round bar specimen was hot-rolled at 1200°C to a plate thickness of 4 mm to obtain a Co-based superelastic alloy material. The hot workability of the Co-based superelastic alloy material was evaluated as described below.

[0063] Furthermore, the Co-based superelastic alloys formed by hot rolling were subjected to solution treatment. Specifically, the alloys other than Alloy No. 122 were heated to 1200°C (solution temperature), and the structure was changed to a single β phase, followed by water cooling (average cooling rate: 1700°C / s). The alloy No. 122 was heated to 1300°C (solution temperature), and the structure was changed to a single β phase, followed by water cooling (average cooling rate: 1700°C / s). The phase state after water cooling and the volume fraction of the β phase are shown in Table 1. In addition, in the notation of "phase" in Table 1, for example, "β+γ" means that in addition to the main β phase, a γ phase was observed at a fraction obtained by subtracting the "volume fraction of the β phase" from 100% (in the case of Alloy No. 105, 26% by volume of the γ phase).

[0064] [Table 1]

[0065] (Hot workability) Of the alloy materials shown in Table 1, the hot workability was evaluated for the alloy materials shown in Table 2. The evaluation results of hot workability are shown in Table 2. In addition, in the hot rolling, those that could achieve a rolling ratio of 60% or more were evaluated as "○" (pass), and those that could not were evaluated as "×" (fail).

[0066] As shown in Table 2, all of the comparative alloys No. 124 to 129 developed cracks during hot rolling and could not be rolled to a rolling ratio of 60%. On the other hand, all of the alloys of the invention examples could be hot rolled without developing cracks.

[0067] [Table 2]

[0068] (Structural observation and crystal structure identification) Figures 2 and 3 show the results of TEM observation (TEM photographs) of alloy No. 120. Note that Figure 2 shows a diffraction pattern (selected area diffraction pattern) when an electron beam is incident on the main phase (β phase) in the [01-1] direction. Also, Figures 3(a) to (d) are electron microscope images of alloy No. 120. Figure 3(a) is a bright-field image obtained using a transmission spot, and Figure 3(b) is a dark-field image obtained in the same field of view using a 111 diffraction spot. Note that Figure 3(c) is a bright-field image obtained using a transmission spot at a different observation location, and Figure 3(d) is a dark-field image obtained in the same field of view using a 200 diffraction spot. The selected area diffraction pattern of the main phase (β phase) with [01-1] incidence shown in Figure 2 indicates that the main phase of Alloy No. 120 has a BCC structure. Furthermore, since the intensity of the 111 diffraction spot in Figure 2 is very weak, it is predicted that the reduced degree of order in the BCC structure results in excellent hot workability.

[0069] (Duplex metal structure) Next, for Alloys Nos. 101 to 104, 120 and 121, after the above-mentioned solution heat treatment, they were cooled at an average cooling rate of 5°C / min to the temperatures shown in Table 3 (temperature ranges in which a multi-phase occurs), and then held for 60 minutes to create a multi-phase metal structure. As a result, as shown in Table 3, it was confirmed that the alloy material obtained a two-phase or three-phase metal structure after being cooled to a temperature range where the two-phase or three-phase structure is formed and then held there.

[0070] [Table 3]

[0071] (Making large particles) Next, using alloy No. 120, the above-mentioned solution heat treatment was performed, and then a grain coarsening process (cycle heat treatment) having a temperature profile as shown in FIG. 4A was performed to produce coarse grains. Specifically, after repeating the heat treatment in the dotted line area shown in FIG. 4A 11 times, in the case of Sample 1, heat treatment was performed at 800°C for 1 hour in the 12th cycle, followed by quenching, and in the case of Sample 2, heat treatment was performed at 800°C for 1 hour in the 12th cycle, followed by heating to 1200°C and then quenching. Next, Sample 1 and Sample 2 were polished, and then observed by electron backscatter diffraction (EBSD) method. The observation results by EBSD are shown in FIG. 4B.

[0072] As shown in Figure 4B, Sample 1 has a four-phase structure consisting of the parent phase β (BCC), σ phase, γ phase, and the ε phase that is transformed by cooling. In addition, the orientation difference map (GROD map) shows that Sample 1 has strain in the parent phase between the precipitates. On the other hand, in Sample 2, as shown in Fig. 4B, it is found that the matrix phase is a single phase of β. However, subgrain boundaries are observed to be formed within the crystal grains, which are predicted to be formed by the strain introduced by the precipitates.

[0073] (plate material) Plates with a thickness of 1.5 mm, width of 8 mm, and length of 70 mm were cut out from the hot-rolled alloy No. 120 and subjected to the cyclic heat treatment (dotted area) shown in Fig. 5A. After the cyclic heat treatment, the plate was subjected to a solution heat treatment at 1200°C for 8 hours and then quenched in water (WQ) (see Fig. 5A). When the cross section parallel to the plate surface of the quenched plate was observed by EBSD, it was found that the crystal grains had become coarse, as shown in Figure 5B, and some of the grains had grown to the point where they had become single crystals. In Figure 5B, the single crystals are shown in dark gray.

[0074] In addition, as shown in Fig. 5B, it was confirmed that the average crystal grain size of the plate material using Alloy No. 120 was equal to or greater than the thickness of the plate material (1.5 mm). This is expected to be due to abnormal grain growth driven by the formed subgrain boundaries, as in the case of conventional Cu-Al-Mn alloy materials. It was found that the above-described method allows single crystal materials to be produced relatively easily.

[0075] (Single crystal) Alloys No. 115, 117 to 120, which are examples of the present invention, and alloys No. 123 to 125, which are comparative examples, were subjected to the cyclic heat treatment shown in FIG. 5A after the above solution heat treatment. Then, analysis was performed by EBSD to evaluate single crystallization. Alloys that obtained single crystals with an average crystal grain size of 1 cm or more were evaluated as "○" (pass), and alloys that did not obtain single crystals were evaluated as "×" (fail). The evaluation results are shown in Table 4.

[0076] (Superelastic properties) As in the evaluation of single crystallization described above, the alloys Nos. 115, 117 to 120 as examples of the present invention and Nos. 123 to 125 as comparative examples were subjected to the cyclic heat treatment shown in FIG. 4A, and the superelastic properties of the obtained samples were investigated using the stress-strain curves.

[0077] When the stress-strain curve of the single crystal sample obtained from Alloy No. 118 was measured, superelasticity was confirmed as shown in Figure 6. Moreover, superelasticity was also confirmed in other examples of the present invention (Alloy Nos. 117 to 120). Furthermore, in the tensile direction <100> In the sample with orientation, the superelastic strain εSE was about 14%, and the total strain εt was 17%. This is more than twice the strain of the Ti-Ni alloy, which is a practical material (conventional material) (see the stress-strain curve "Ti-Ni RANDOM" in the lower left of Figure 6), and is about four times the deformation amount of the β-Ti-based shape memory alloy (Ti-Nb-Ta-Zr alloy) (see the stress-strain curve "Ti-Nb-Ta-Zr <101> (See “Textured”)

[0078] Moreover, the orientation dependence of the superelastic properties of the single crystal specimen obtained from alloy No. 120 is shown in FIG. 7A. <110> In the sample of orientation, <100> The critical stress increased and the deformation strain decreased compared to the samples with the axial orientation. <111> In this orientation, superelasticity was not obtained because the critical stress exceeded the material's own fracture stress.

[0079] With regard to the superelastic properties and orientation dependency, the invention alloys No. 115, 117, and 119 also showed favorable results similar to those of alloys No. 118 and No. 120. However, in the comparative alloys No. 123 to 125, as shown in Table 4, single crystals could not be produced, and polycrystals were obtained, so that superelastic properties could not be obtained due to grain boundary fracture.

[0080] Here, the stress-strain curve (SS curve) in this example was obtained as follows: First, a tensile test piece having the dimensions shown in Fig. 7B was subjected to loading and unloading of stress twice in a tensile test to obtain a stress-strain curve.

[0081] [Table 4]

[0082] (Elastic deformation properties) Single crystal samples were prepared by subjecting alloys No. 118 and 120 to the cyclic heat treatment shown in Fig. 5A. The elastic deformation region of these single crystals was measured using a strain gauge, and stress-strain curves were obtained (Fig. 8A). In the tensile direction <100> In the single crystal samples with oriented orientation, alloy No. 120 showed a very large elastic deformation, approximately 4.5%, and alloy No. 118 showed a very large elastic deformation, approximately 2.5%, compared to normal metallic materials. In both alloys No. 118 and 120, martensitic transformation occurred after normal elastic deformation, and they showed superelasticity.

[0083] Furthermore, when the Young's modulus was calculated from the differential value of the stress-strain curve (Fig. 8A) of each single crystal sample of Alloy No. 118 and 120 in accordance with JIS Z 2280, both had a low Young's modulus of approximately 10 to 30 GPa, which is very close to that of living bone, as shown in Fig. 8B.

[0084] Fig. 9 shows the stress-strain curve of the single crystal sample obtained from alloy No. 120, and the relationship between Young's modulus and strain obtained from the stress-strain curve. As shown in Fig. 9, the Young's modulus of alloy No. 120, which is an example of the present invention, differs depending on the orientation, <110> Nearby <111> The samples in the vicinity showed higher values ​​of 80 GPa and 120 GPa, respectively. <111> It is predicted that an even higher Young's modulus can be obtained by approaching the direction.

[0085] (Wear characteristics) Next, in order to evaluate the wear characteristics of the alloys Nos. 118 and 120 after the above solution treatment but before the cyclic heat treatment, a ball-on-disk wear test was carried out. Specifically, a sample was cut to a thickness of 5 mm, and a carbide ball (tungsten carbide ball) with a diameter of 3 / 16 inch (4.7625 mm) was used as the counter material. A load of 3 kg was applied to the sample, and the sample was slid along a circumference with an abrasion radius of 3 mm at a speed of 50 mm / s for 1 hour to perform an abrasion test. As comparative examples, similar tests were also conducted on Co-Cr-Mo alloy (Alloy No. 130), SUS316L (Alloy No. 131), CP-Ti (Alloy No. 132), and Ti-6Al-4V alloy (Alloy No. 133), which are primarily used as metal materials for biomedical applications.

[0086] Photographs of the wear marks and cross section after the wear test are shown in Figure 10. Although it is slightly inferior to the Co-Cr-Mo alloy (Alloy No. 130), which has excellent wear resistance, it is clear that the amount of wear is extremely small compared to SUS316L (Alloy No. 131), Ti-6Al-4V alloy (Alloy No. 133), and CP-Ti (Alloy No. 132). In addition, the specific wear rate (wear volume / sliding distance / load), which is the wear rate per unit load, was determined as the wear characteristics. Specifically, the specific wear rate was calculated by calculating the wear volume from the cross-sectional area and wear radius calculated from the cross-sectional image shown in Figure 10, and then calculating it from the sliding distance and load. The results are shown in Table 5. The unit of the specific wear rate shown in Table 5 is "×10 -8 (mm 2 / N).

[0087] [Table 5]

[0088] (β phase crystal structure) Next, the influence of the average cooling rate in the cooling process after the solution treatment on the crystal structure of the β phase was investigated using alloy No. 120. Specifically, alloy No. 120 was first heated to 1200°C (solution temperature) to convert the structure to a single β phase, and then cooled at the average cooling rate shown in Table 6. The phase state after cooling, the volume fraction of the β phase, and the proportion (volume %) of the B2 phase in the β phase are shown in Table 6. In addition, in the notation of "phase" in Table 6, for example, "β+γ+σ" means that in addition to the main β phase, a fraction of (γ+σ phase) was observed, which is calculated by subtracting the "volume fraction of the β phase" from 100%.

[0089] As shown in Table 6, the higher the average cooling rate in the cooling process, the higher the proportion of the B2 phase in the β phase. All of the inventive examples, in which the average cooling rate was 5°C / sec or more, exhibited excellent superelastic properties and processability. On the other hand, all of the comparative examples, in which the average cooling rate was less than 5°C / sec, exhibited poor superelastic properties and processability.

[0090] [Table 6]

Claims

1. A Co-based superelastic alloy material made of a Co-Cr-Al-Si alloy, The composition (atomic percent) is On the Co-Cr-(Al,Si) pseudo-ternary phase diagram, Point A: Co 49.5 Cr 27.5 (Al, Si) 23 , Point B: Co 57 Cr 27.5 (Al, Si) 15.5 , Point C: Co 50 Cr 45 (Al, Si) 5 , D point: Co 45 Cr 45 (Al, Si) 10 , and Point E: Co 45 Cr 32 (Al, Si) 23 and wherein the content of Al is 2.5 to 10.0 atomic % and the content of Si is 2.5 to 13.0 atomic %.

2. 2. The Co-based superelastic alloy material according to claim 1, characterized in that the main phase of the metal structure is a β phase with a BCC structure.

3. 3. The Co-based superelastic alloy material according to claim 2, wherein a volume fraction of the β phase of the BCC structure is 50% or more.

4. 4. The Co-based superelastic alloy material according to claim 2 or 3, characterized in that in addition to the main phase, it contains one or more phases selected from the group consisting of a γ phase of an FCC structure, an ε phase of an HCP structure, and a σ phase, in a total amount of 50 volume % or less.

5. The crystal structure of the β phase is A2 phase, B2 phase and L2 phase. 1 5. The Co-based superelastic alloy material according to claim 2, characterized in that it is composed of one or more phases selected from the group consisting of:

6. 6. The Co-based superelastic alloy material according to claim 5, wherein the B2 phase accounts for 20 volume % or more of the β phase.

7. A plate material made of the Co-based superelastic alloy material according to any one of claims 1 to 6, characterized in that the average crystal grain size of the Co-based superelastic alloy material is equal to or greater than the thickness of the plate material.

8. 7. A wire made of the Co-based superelastic alloy material according to claim 1, wherein an average crystal grain size of the Co-based superelastic alloy material is equal to or greater than a radius of the wire.

9. A method for producing a Co-based superelastic alloy material according to any one of claims 1 to 6, comprising a solution heat treatment step of performing heat treatment at 1100°C to 1400°C.

10. 10. The method for producing a Co-based superelastic alloy material according to claim 9, further comprising a cooling step of cooling the material to room temperature at an average cooling rate of 5[deg.] C. / sec or more after the solution heat treatment step.

11. 11. The method for producing a Co-based superelastic alloy material according to claim 10, further comprising a grain coarsening process, between the solution heat treatment process and the cooling process, in which the temperature range in which the alloy becomes a single β phase, and a temperature range in which the alloy becomes two phases, β phase + γ phase or β phase + σ phase, or a temperature range in which the alloy becomes three phases, β phase + γ phase + σ phase, are repeatedly heat-treated.

12. The method for producing a Co-based superelastic alloy material according to claim 11, characterized in that the temperature range in which the single β phase occurs is a temperature range of 1100 to 1400°C, and the temperature range in which the two phases occur or the temperature range in which the three phases occur is a temperature range of 700 to 1100°C.

13. A guide wire comprising a material containing the Co-based superelastic alloy material according to any one of claims 1 to 6.

14. A stent comprising a material containing the Co-based superelastic alloy material according to any one of claims 1 to 6.

15. An artificial hip joint, comprising a material containing the Co-based superelastic alloy material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • High temperature resistant protective layer alloy

    JP1984118847A

  • Digital filter

    JP1989090608A